A domain decomposition technique for acoustic wave interactions and scattering - Lim, Wei Xian (2024)
In this work, a two-dimensional domain decomposition technique (DDT) is developed based on an overset method that couples a nonlinear Euler solver with a linearized Euler solver. The nonlinear domain accounts for complex physics in the near field, such as acoustic wave interaction with shock waves and acoustic wave scattering from solid bodies. The linear domain allows the small perturbation waves induced by the nonlinear effects to propagate with minimal numerical dissipation and dispersion while also significantly reducing computational resources. To this end, two scenarios have been considered: (i) wave amplification and modulation in a converging-diverging duct with a standing shock wave and (ii) wave scattering from an incident acoustic wave over a supercritical airfoil. With DDT, these cases show a reduction in computational time by more than 70% compared to their respective fully-nonlinear simulations. The accuracy of the simulations with DDT is found to depend on the extent of overlap between the linear and nonlinear zones. In general, an overlap ratio of at least two is necessary to maintain high order of convergence rate, though still limited by the nonlinear scheme. Furthermore, the implementation of DDT in the external flow case can eliminate numerical noise observed at the far field of the fully-nonlinear counterpart, which do not have any effective non-reflecting boundary treatment.